(untitled) (Fiep Bulletin - online, 2013)
Several equations are found in the literature, whether specific or widespread, in the intuit of predicting the density and/or the body fat. It objectives to describe aspects involved in the development process, validation and possibilities of applications of the predictive equations of the body fat. A bibliographical investigation was carried out in the scientific literature using the following terms: body composition, body density, body fat, anthropometric, hydrostatic weighing, AXDE, equations predicative and validation. 197 Volume 79 - Special Edition - ARTICLE I - 2009 FIEP BULLETIN FIEP BULLETIN Volume 79 - Special Edition - ARTICLE I - 2009 National and international articles were found in the databases of PubMed, LILACS and Scielo, as well as books. The data of this review allow standing out that the anthropometrics methods, skinfolds, circumferences and diameters are habitually used in the predictive equations to estimate the density and/or the body fat, as well as the hydrostatic weighing and the absorptiometry x-ray of dual energy (AXDE), methods that are considered “Gold Standard". The equations of Durnin & Wormersley, Jackson & Pollock and Jackson et al. are enough used in Brazil. In the development and validation of the predictive equations, technical regression statistics is used (lineal simple or multiple), the correlation of Pearson (r), the paired t test, the standard estimation error (SEE), the total error (TE), the constant error (CE), the diagnostic analysis of the residual of Zar, as well as the method of Bland and Altman. To be perceived that the one taken of decision in the selection of a prediction equation of the body fat is not so easy. It is needed enough caution being necessary to know the reality for which the equation was developed and in which it will be applied, its validity, practicity, advantages and limitations.